Álcool e comportamento: efeitos na aprendizagem e memória - Chacon, Diana Marques Martins (2013)
Excessive alcohol consumption is responsible for many harmful effects on individuals and society. Despite years of research, the mechanisms by which alcohol affects neurological functions and the exact causes of cognitive impairment related to long-term use are unknown. In this sense, this master study proposed to observe how different doses of alcohol affect the addiction response and the learning ability of two fish species: Betta splendens and Danio rerio, the latter a commonly model due to organizational and functional characteristics shared with mammals. For this, different concentrations of ethanol (0%, 0.1%, 0.25%, 1% and 1.5%) were used in acute, chronic and withdrawal treatments. We tested the fish in three experimental protocols: 1) alcohol addiction potential using conditioned place preference, 2) associative conditioning using light as unconditioned stimulus and food as conditioned stimulus and 3) spatial learning using a maze without cues. For the alcohol addiction potential, preference between two different places in a shuttle box was tested before and after alcohol exposure (chronic and acute). In this test, the animals intoxicated by 0.1% did not change behavior, while animals receiving 1% and 1.5% alcohol changed the initial preference to the side where they received alcohol For the associative conditioning, the results show that the groups undergoing low dose (0.1%), both in chronic and withdrawal treatment, learned the task faster than control; groups under 0.25 and 1% alcohol withdrawal learned the task after control; groups chronically intoxicated with these doses did not learn the task. For the spatial learning test, fish submitted to acute and chronic treatments decreased the time to exit the maze; there were significant differences in the animal s performance in a dose-dependent pattern. This difference was not observed for the withdrawal treatment. Given these results, we conclude that the effects of alcohol on learning are dependent on the dosage. Furthermore, low doses of alcohol seem to maximize animal performance on learning tasks and do not alter their seeking behavior, while higher doses induced addition and hinder learning